Study the influence of yogic asana on body composition and cardiopulmonary functions of adolescent girls - Indranil Manna (Wolters Kluwer Medknow Publications, 2020)
INTRODUCTION: Inadequate physical activity leads to obesity, diabetes, and cardiopulmonary dysfunctions. Adolescent girls undergo certain changes during this phase of life. Yoga exercises can help to develop their body composition and physiological status and thus maintain good health. AIM: The present investigation aimed to see the influence of yogic asana on subcutaneous adipose tissue and cardiopulmonary functions of adolescent girls. MATERIALS AND METHODS: A total of 87 girls (age: 12-14 years) were screened, of whom 27 were excluded from the study after medical examinations and the remaining 60 volunteers were grouped randomly into (i) yoga group (n = 30) and (ii) control group (n = 30). The yoga group followed a yoga training of 60 min/day, 6 days/week for 12 weeks with no yoga training in the control group. RESULTS: The 12 weeks of yogic training showed an increase (P < 0.05) in forced expiratory volume in 1 s (FEV1), forced vital capacity (FVC), peak expiratory flow rate (PEFR), maximum ventilatory volume (MVV), and breath-holding time (BHT), with reduction (P < 0.05) in subcutaneous adipose tissue (body fat), systolic blood pressure (SBP), resting heart rate (RHR), and respiratory rate (RR) among the yoga group participants. On the other hand, the yoga group exhibited a higher (P < 0.05) level of FVC, FEV1, PEFR, MVV, and BHT and lower (P < 0.05) subcutaneous adipose tissue, SBP, diastolic blood pressure, and RR when compared to the control group after 12 weeks of study. CONCLUSIONS: Regular practice of yogic asana helps to lower subcutaneous adipose tissue and enhance the cardiopulmonary fitness of adolescent girls, which may reduce the expanses toward medication and increase the productivity.